GEOCHEMICAL MODEL OF PRECAMBRIAN GRANITOID MAGMATIC EVOLUTION IN THE KOROSTEN PLUTON (UKRAINIAN SHIELD): PETROGENETIC ASPECTS AND GENESIS OF COMPLEX ORE MINERALIZATION IN METASOMATIC ZONES - Shnyukov, S.; Lazareva, I.; Zinchenko, O.; Khlon, E.; Gavryliv, L.; Aleksieienko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Preliminary geochemical dataset for the granitoids (rapakivi, granite-porphyries, veined granites) of Korosten anorthosite-rapakivi granite pluton (Ukrainian Shield) was studied. The data set includes the results of all major and selected trace elements determinations (XRF, >300 samples), and is compared with melt crystallization and partial melting models of trace elements behavior. Only the Rayleigh model closely approximates the trace element data for granitoids. Typical incompatible behavior under approximately constant bulk distribution coefficient is determined for Rb (DRb = 0,5). Model f values (weight fraction of liquid in magma chamber) are calculated for each granitoid type (residual melt portion) from Rayleigh equation and Rb content in rocks (CRb) assuming minimum concentration in granitoids (169 ppm) as Rb content in parent magma (C0Rb). C vs. f curves for trace (including P, Ti, S, Cl, F, Ca) and major elements are approximated by means of equations of CC0?fD-1 form or polynomial ones respectively. This set of equations is an idealized model of element behavior that demonstrates the depletion of Ba, Sr, Ti, Zr, P, S and enrichment of Th and Ga in the residual liquid as well as the inversion behavior of LREE, Y, F, Cl, Nb, Zn and Pb during the melt fractional crystallization in magma chamber. Monotonous decrease of both Zr and P content indicates melt saturation in zircon and apatite. Therefore, model temperature (Tmodel) of the melt is estimated from equations of zircon and apatite solubility. The temperature evolution in magma chamber was presented as Tmodel vs. f polynomial equation (Tmodel range: 900-720oC). Inversion in LREE content (f = 0,185) indicates the apatite/monazite replacement in the crystallizing assemblage. Water content in melt for this f value and corresponding Tmodel was calculated from equation of monazite solubility which demonstrates its high H2Odependence. C0H2O=2,36 wt% was estimated on this basis (assuming DH2O = 0,1) for the liquidus of initial granite melt (Ptotal ~6,3 kbar). According to designed model water saturation limit was reached at f = 0,165 and H2O-fluid was extracted from the melt during its further evolution. Synchronous inversion of C/C0 vs. f curves shows the enrichment of fluid with F, Cl, Nb, Zn, Pb etc. Such characteristics of fluid are in agreement with geochemical data for ore-bearing altered rocks and might testify for their genetic unity.
Keywords: granite; rapakivi; trace element; magmatic evolution; apatite; zircon; monazite; xenotime; solubility; water in melt; fluid extraction; altered rocks; ore mineralization